Mapping the intersection of fast fashion and climate change: A bibliometric analysis of publication trends, key contributors and research themes - Rosely, Nurhidayah; Abdullah Thani, Ayu Kamareenna; Sakarji, Siti Rosnita; Mohd Firdaus Kozako, Intan Nurul’Ain (Journal of Islamic, Social, Economics and Development, 2026)
The fast fashion industry has increasingly been recognised as a significant contributor to climate change, prompting growing scholarly attention across sustainability, environmental management, and business research. This study systematically examines the evolution, structure, and thematic development of scientific literature at the intersection of fast fashion and climate change between 2010 and 2025 using a bibliometric approach. A total of 2,697 peer-reviewed journal articles indexed in the Scopus database were analysed following established identification, screening, and eligibility procedures. Data visualisation and science mapping were performed using VOSviewer (v.1.6.20) to analyse the keyword occurrence patterns. To enhance analytical clarity, a minimum occurrence threshold was applied to filter salient keywords and reveal dominant research clusters. The findings indicate a pronounced acceleration in publication output after 2020, reflecting heightened academic and societal concern regarding climate impacts, sustainability, and responsible production within the fast fashion sector. The literature is concentrated within a small number of sustainability-oriented journals, supported by a core group of recurring contributors from interdisciplinary backgrounds such as supply chain management, environmental science, and sustainable business. Keyword mapping reveals four major thematic clusters, highlighting established research streams related to environmental impacts, sustainable supply chains, circular economy practices, and emerging discussions on governance and systemic change. This study contributes to the literature by providing a comprehensive overview of the intellectual landscape of fast fashion and climate change research, identifying dominant themes and research gaps, and offering a structured foundation for future theoretical and empirical investigations.